2022
DOI: 10.1111/cas.15257
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of cannabidiol via TRPV2 channel in chronic myeloid leukemia cells and its combination with imatinib

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…We recently demonstrated the expression of TRPV1 on K562, KU812, and MOLM-6 CML cell lines, common myeloid progenitors, normal myeloid cell enrichment, and PBMCs, respectively ( Maggi et al, 2022 ). To enhance our analysis of TRPV1 expression, we have also performed in silico analyses with datasets 6326/6610 from the Stemformatics database and GSE13159 from the GEO repository, demonstrating its expression in all types of leukemia cells ( Supplementary Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated the expression of TRPV1 on K562, KU812, and MOLM-6 CML cell lines, common myeloid progenitors, normal myeloid cell enrichment, and PBMCs, respectively ( Maggi et al, 2022 ). To enhance our analysis of TRPV1 expression, we have also performed in silico analyses with datasets 6326/6610 from the Stemformatics database and GSE13159 from the GEO repository, demonstrating its expression in all types of leukemia cells ( Supplementary Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…In this tumor type, it has only been demonstrated that the activation of TRPV5 and TRPV6 promotes a Ca 2+ -dependent cell cycle arrest ( Heise et al, 2010 ), and the inhibition of TRPM7 impairs cell proliferation and stimulates erythroid differentiation in K562 cells ( Takahashi et al, 2018 ). In addition, we recently showed that TRPV2 activation induced mitophagy associated with cell growth inhibition and stemness reduction in chronic myeloid leukemia (CML) cells ( Maggi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the fact that TRPV2 and TRPV4 have very similar gene sequences, Huang et al found that CBD interacts with residues on the S6 helix of TRPV4, thus suggesting that TRPV4 plays an important role in CBD inhibition of glioma ( Huang et al, 2021 ). Maggi et al confirmed using cell growth and other assays that CBD can inhibit the proliferation and cycle of chronic myeloid leukemia cells through the TRPV2 channel ( Maggi et al, 2022 ).…”
Section: Studies On Regulation Of Transient Receptor Potential Channe...mentioning
confidence: 99%
“…Cannabidiol exerts a synergistic effect with imatinib in imatinib-resistant CML cells. 354 In AML carrying FLT3-ITD, FLT-3-ITD molecules were detected in the autophagosome after induction of autophagy with the proteasome inhibitor bortezomib. It suggests that autophagy is involved in the posttranslational degradation of aberrant PTKs, and induction of autophagy is undoubtedly beneficial in this case.…”
Section: Mechanisms Of Tki Resistancementioning
confidence: 99%